(3TQM QSGdI CHj GdUdJ aj GdYed HGdGSWQdGHs - (3eLghds ((3GdbSWfWjfjIs)
(3ChdgG (B:s
(3GdMeO ddg agPG aj cjajI GdYed HGdGSWQdGH GdTeGdj ; GdGSWQdGH GdTeGdj ef GdBdGJ GdeTghQGJ LOG aj cd UfY hCcKQhG GdfGS aj GdYed Hg GdJUGfja (B, (3bGd eUfag hCLhO eG WGdYJg ef cJH GdYed Hg cJGH CHh GdUdJ s
(3BNQgG (B:s
(3GdaUd GdKeGfhf (B: (3ajeG jJYdb HGdTHcI hCeG eG jJYdb HGdTHcI hGdebfWQQGJ hGdSJehJ hGdGQJaGY eKd GSJNQGL GdLgGJ GdCQHY Ch dHYVgG cGfMQGa GdHdOGf hSYI GdeTGQb hCTHGgg jSJYGf aj Pdc HGdLjhH hGddg CYde s
(3JGQjN GdfSN eDQN HMSGH GdLed dcf cdeGJg djSJ ebQhAIs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3Gdadc hGdJfLje hGdejbGJs